Textual Intimacy : Autobiography and Religious Identities - Kort, Wesley A. (Book collections on Project MUSE., 2012)
"Given its natural affinity with questions of identity, autobiography offers a way into the interior space between author and reader, especially when writers define themselves in terms of religion. In his exploration of this 'textual intimacy, ' Wesley Kort begins with a theorization of what it means to say who one is and how one's self-account as a religious person stands in relation to other forms of self-identification. He then provides a critical analysis of autobiographical texts by nine contemporary American writers--including Maya Angelou, Philip Roth, and Anne Lamott--who give religion a positive place in their accounts of who they are. Finally, in disclosing his own religious identity, Kort concludes his journey with a meditation on several meanings of the single word assumption."--Page 4 of cover.